Leadership and Management : Global Warming Impact on Policing: An analysis of security preparedness - Mayar, Ring (IJRDO-Journal of Applied Science, 2017)
In recent years a range of provocative thinkers have gathered in Canberra to debatethe impact of climate change on law enforcement beyond the 21st century. For nearly acentury, the police strategies have remained unchallenged. Police or security agenciesinterchangeably have engaged in parallel strategies to prepare for the emerging issues andenabled them to carry out their duties responsibly. Nowadays, the climate change concernremains as the most futuristic obstacle that will pose serious problem to policing. The lawenforcement agencies previously have always enjoyed the privilege to acquire limitlessinformation, share ideas and experiences worldwide, to have adequate education and trainingopportunities, and so developing a better understanding of police future conflict dimensions.However, the flip side of the coin is that the entire world is quickly confronted with climatechange threats (Abbott, 2008), emerging security issues from various social, environmentaland political influences which did not previously fall under conventional notions of“defence”. Within the next two decades, the demands for policing and expectation will be fargreater and more complex. Moreover, police leadership will be hit with high demands formulti skilled forces and resources constraints. In addition, operational ambiguity willcontradict leadership strategic planning to achieve civility, order and security. The influx ofclimate change refugees from neighbouring islands may contribute to the causes of violenceand unruly behaviour. In this situation, modern police skills, resources to high expectation toserve the community should not be overlooked. Therefore, it is vital for the future leadershipin policing to identify those key trends that will demand law enforcement diligence inachieving maximum expenditure of efforts and resources.